The Om(1E) mutation in Drosophila ananassae causes compound eye overgrowth due to tom retrotransposon-driven overexpression of a novel gene. - Juni, N.; Awasaki, T.; Yoshida, K.; Hori, S.H. (Genetics, 1996)
Optic morphology (Om) mutations in Drosophila ananassae are a group of retrotransposon (tom)-induced gain-of-function mutations that map to at least 22 independent loci and exclusively affect the compound eye morphology. In marked contrast to other Om mutations, which are characterized by fewer-than-normal and disorganized ommatidia, the Om(1E) mutation exhibits a peculiar phenotype as enlarged eyes with regularly arrayed normal ommatidia. To characterize the Om(1E) mutation, we have carried out molecular analyses. A putative Om(1E) locus cloned by tom tagging and chromosome walking contained two transcribed regions in the vicinity of tom insertion sites of the Om(1E) mutant alleles, and one of these regions was shown to be the Om(1E) gene by P element-mediated transformation experiments with D. melanogaster. The Om(1E) gene encodes a novel protein having potential transmembrane domain(s). In situ hybridization analyses demonstrated that the Om(1E) gene is expressed ubiquitously in embryonic cells, imaginal discs, and the cortex of the central nervous system of third instar larvae, and specifically in lamina precursor cells. Artificially induced ubiquitous overexpression of Om(1E) affected morphogenesis of wing imaginal disc derivatives or large bristle formation. These findings suggest that the Om(1E) gene is involved in a variety of developmental processes.